Penerapan Konsep Lean Warehousing untuk Minimasi Pemborosan Gudang Suku Cadang dengan Metode VSM Pada PT ABC - Adjietama, Mochammad Novrizal; Nur Rahmawati (Jurnal Serambi Engineering, 2025)
PT ABC is a company operating in the fertiliser industry and plays a vital role in supporting the national agricultural sector. One of the key elements in maintaining smooth operations is warehouse management, which encompasses the processes of receiving, storing and distributing materials. Efficient warehouse management is essential to ensure the smooth flow of materials, minimise waste and support overall operational efficiency. This study aims to analyse and identify waste in PT ABC's warehouse using the Lean Warehousing approach and the Value Stream Mapping (VSM) method. Initial analysis shows that the Process Cycle Efficiency (PCE) value of 68.92% indicates potential waste within the warehouse activities. The main sources of waste were identified in activities such as unloading goods, reconciling item data with the system and preparing administrative documents. Improvement alternatives were implemented using the 5S principles, including sorting (seiri), reorganising the warehouse layout (seiton), routine cleaning (seiso), standardising SOPs (seiketsu) and promoting a culture of discipline (shitsuke). With these improvements, the estimated PCE increased to 80.11%, reflecting an efficiency improvement of 11.19%. This study shows that the implementation of Lean Warehousing is effective in optimising warehouse management at PT ABC.